Ogilvie’s Syndrome in A Young Adult with HIV Infection: A Case Report - I Made Gede Dwipayana Putra; Ketut Suryana (Universitas Pendidikan Ganesha, 2026)
Acute colonic pseudo-obstruction, known as Ogilvie’s syndrome, is a condition characterized by acute colonic dilation in the absence of mechanical obstruction. Primary clinical feature is abdominal distension. Abdominal pain is present in 80% of cases, followed by nausea and vomiting in approximately 60%. Diagnosis can be found from clinical symptoms, laboratory tests, and radiological imaging. Plain abdominal X-ray is a good diagnostic tool. A 27-year-old male patient was hospitalized at district hospital with complaints of fever for 2 days before admission, previously fever for 2 weeks, accompanied by abdominal pain, inability to fart and defecate in the last 4 days, abdominal distension previously existed. Laboratory examination found anemia, leukopenia, thrombocytopenia, hyponatremia and hypokalemia. Plain abdominal X-ray examination found a colonic dilatation with an impression of adynamic ileus. Ogilvie’s Syndrome is a clinical condition characterized by abdominal distension and dilation of the colon. This condition can occur at younger age, especially in those with serious medical conditions or a history of surgery. In this 27-year-old male patient, he had a serious medical condition, HIV, which caused a compromised immune system, which could be the reason of Ogilvie’s Syndrome. HIV/AIDS is a chronic immune system disorder that causes various multi-organ manifestations, has very serious consequences and can develop to Ogilvie’s Syndrome.